Inorganic Hollow Nanocoils Fabricated by Controlled Interfacial Reaction and Their Electrocatalytic Properties (Small 44/2021). Issue 44 (4th November 2021) - Moon, Jun Hwan; Lee, Moo Young; Park, Bum Chul; Jeon, Yoo Sang; Kim, Seunghyun; Kim, Taesoon; Ko, Min Jun; Cho, Kang Hee; Nam, Ki Tae; Kim, Young Keun
Abstract : Inorganic Hollow Nanocoils In article number 2103575, Ki Tae Nam, Young Keun Kim, and co‐workers explore the electrochemical strategy to fabricate the 3D metal‐based hollow nanocoils (HNCs) based on controlling the solid‐liquid interfacial reaction. Mn‐based HNC composite shows increased electrochemical water oxidation efficiency through increasing the active sites. With a broad vision, the authors foresee that the use of the HNCs is arriving with more innovative evolutions.